Digested sludge-derived three-dimensional hierarchical porous carbon for high-performance supercapacitor electrode. Issue 4 (11th April 2018) - Zhang, Jia-Jia; Fan, Hao-Xiang; Dai, Xiao-Hu; Yuan, Shi-Jie
Abstract : Digested sludge, as the main by-product of the sewage sludge anaerobic digestion process, still contains considerable organic compounds. In this protocol, we report a facile method for preparing digested sludge-derived self-doped porous carbon material for high-performance supercapacitor electrodes via a sustainable pyrolysis/activation process. The obtained digested sludge-derived carbon material (HPDSC) exhibits versatile O-, N-doped hierarchical porous framework, high specific surface area (2103.6 m 2 g −1 ) and partial graphitization phase, which can facilitate ion transport, provide more storage sites for electrolyte ions and enhance the conductivity of active electrode materials. The HPDSC-based supercapacitor electrodes show favourable energy storage performance, with a specific capacitance of 245 F g −1 at 1.0 A g −1 in 0.5 M Na2 SO4 ; outstanding cycling stability, with 98.4% capacitance retention after 2000 cycles; and good rate performance (211 F g −1 at 11 A g −1 ). This work provides a unique self-doped three-dimensional hierarchical porous carbon material with a favourable charge storage capacity and at the same time finds a high value-added and environment-friendly strategy for disposal and recycling of digested sludge.